Individual identity and cultural unlocking: Consequences of changing performance management in organizations - Gabriele Faßauer (Technische Universität Chemnitz, Professur für Organisation und Arbeitswissenschaft, 2005)
The purpose of the present paper is to examine new performance management patterns in regard to their consequences for the individual identity of organizational members. In modern societies values and norms of individual performance and success play a crucial role for the constitution of individual identity. Related to the German context the paper shows that the present tendency of the finalization of performance criteria and their simultaneously increasing fluid or dynamic character question conventional notions about good performance and justified social and material success. Therefore, these tendencies indicate an unlocking process in organizations which affects the individual identity of organizational members in a fundamental way. In line with this reasoning the paper presents a framework to describe possible effects on identity, the resulting performance acting and the consequences for the organization in general.
urn:nbn:de:101:1-2008071582
Keywords: 650; Leistungsprinzip; Personalbeurteilung; Unternehmensethik; Soziale Werte; Theorie